The collaborative factory of the future. Issue 1 (2nd January 2017) - Moghaddam, Mohsen; Nof, Shimon Y.
Abstract : This work is a contribution to the ever-evolving concept of factory of the future (FoF); thinking about its challenges, and how we can best accomplish its promise. Globalised economies, competitive, volatile and complex business environments have gradually transformed modern manufacturing processes into highly distributed but interconnected networks of entities, which divide their responsibilities and core competencies to sustain and evolve. To achieve these ends, collaboration among networks of intelligent and autonomous entities must be effectively engineered and augmented. In view of that need, a formalism of the collaborative control theory (CCT) is developed in this article, based on the state-of-the-art advances in its design principles, supported by collaborative e-Work and their roles in engineering augmentation of collaboration. Several specific examples of e-Manufacturing systems ( e-Factories ) are used to elaborate further the mechanics of the developed formalism. The goal is to provide a framework of the collaborative factory of the future (CFoF). This framework is applied to enable the abstraction of disparate e-Factories as collaborative networks of entities, which in turn can be engineered and augmented through the CCT operators in order to address the FoF-2020 challenges of scalability and sustainability.